Kebijakan Perlindungan Anak: Persepsi Orang Tua Suku Bajo Terhadap Kebijakan Gizi Seimbang Bagi Anak Remaja - Ruslan Halifu; R. Nunung Nurwati; Binahayati Rusyidi; Santoso Tri Raharjo (Universitas Teuku Umar, 2020)
This study aims to find out perception of Bajo parents who has teenager (in Bajo Bahari Village, Wabula District, Buton Regency, Southeast of Sulawesi) to balanced nutrition policy and to find out relation of it perception. This study using a quantitatif method. The responden of this study is mothers of teenager in Bajo Bahari Village. The responden of this study selected under purposively sampling technique. The instrument of this study is the questionnaire. The data obtained were analyzed using SPSS program. The results showed that 83 % respondents has perception to balanced nutrition policy is negative and 17 % respondents has perception to it policy is positive. It caused by their knowledge about balanced nutrition that less. This study given scientific information that community who has perception to balanced nutrition that negative still available until now. They usually have the culture that unique, as example is Bajo Tribe in Bajo Bahari Village.